Ion transport and association study of glyme-based electrolytes with lithium and sodium salts. (1st May 2019) - Morales, Daniel; Ruther, Rose E.; Nanda, Jagjit; Greenbaum, Steven
Abstract: Glyme solvents are a promising avenue of research in novel electrolytes, due to their thermal and chemical stability, large electrochemical window, and tunable properties. This work investigates the transport properties of LiPF6 and NaPF6 salts in Monoglyme (G1), Diglyme (G2), and Tetraglyme (G4). Self-Diffusion coefficients, and degrees of ion association were found through spectroscopic techniques. Raman and Fourier-Transform Infrared (FTIR) spectroscopy exhibited an absorbance peak at 740 cm −1, corresponding to the a1g mode; known to signify the presence of solvent-separated and contact ion pairs. The increased intensity of this peak for G1 compared to G4 suggests that the electrolyte exhibits stronger association with decreasing solvent size. Nuclear Magnetic Resonance Diffusometry measurements yield self-diffusion coefficients for 7 Li, 23 Na, and 19 F across all samples to be on the order of 10 −9 m 2 s −1 in G1, to 10 −11 m 2 s −1 in G4. Comparison of conductivities calculated from the measured diffusivities and the Nernst-Einstein equation with conductivity measurements deduced from Electrochemical Impedance Spectroscopy (EIS) determined the ion association degree; the electrolytes were shown to exhibit stronger ion pairing with increased temperature which is attributed to a decrease in the dielectric constant of the solvents with increasing temperature. Additionally, the ion association was shown to decrease with increasing solvent molecular size, consistent with FTIR findings. Highlights: NMR spectroscopy probed ion transport and association in PF6 -based electrolytes. Results from NMR were compared to analysis of vibrational spectra. Ion association decreases with increasing chain length of the glymes. All electrolytes showed increasing ion association with increasing temperature. Conductivity decreased at high temperatures in monoglyme due to strong ion pairing.